The Abloviak shear zone and the NW Torngat Orogen, eastern Ungava Bay, Québec. - Goulet, Normand; Ciesielski, André (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The NW-trending Torngat Orogen in eastern Ungava Bay, which contains Early Protero-zofc sedimentary rocks and Archean ortho-gneiss, is subdivided into the Burwell terrane, Tasiuyak gneiss, Lake Harbour Group and the George River segment. The Burwell terrane. a granulite-facies migmatitic complex, grades to the southwest into the Tasiuyak gneiss composed of plagioclase-garnet-quartz-sillimanite and graphite. Further to the southwest, the Tasiuyak gneisspasses gradationally into amphlbolite-faciespelitic gneiss, quartz!te and marble of the Lake Harbour Group, which is associated with granodioritic Archean orthogneiss of the George River segment. The 15 km wide Abloviak shear zone, a high strain zone with-in the eastern Torngat Orogen, overprints and subvertically transposes the Tasiuyakgneiss, part of the Lake Harbour Group and its Archean basement. D, deformation is interpreted to have resulted In development of early foliation, and west- to southwest-verging thrusts that interleaved Lake Harbour Group rocks and George River segmentgneiss. D2 was a transpressional deforma-tion event responsible for refolding in the Lake Harbour Group and development of mylonitic fabrics in the Abloviak shear zone.The latter comprises medium- to highly strained rocks (mylonites) formed in a major transcurrent sinistral shear environment. The Lake Harbour Group is deformed into km-scale NNW-trending dome-and-basin structures, involving Archean basement, that were vertically transposed in a northwest ward direction toward the Abloviak shear zone.